What is -12 / 3 * (-8+(-4)^2 -6) +2 simplified?

6 answers

I already have the answer. I just couldn't find out how to do the step by step process. If you are wondering how I got the answer; I tried to do the work first, then I checked my work out on multiple online calculators.
-12 / 3 * (-8+(-4)^2 -6) +2
PEMDAS
-12 / 3 * (-8+16 -6) +2
-12 / 3 * + 2 + 2
-4 + 4 = 0
-12 / 3 * (-8+(-4)^2 -6) +2
= -4 * (-8+16-6) + 2
= -4 * 2 + 2
= -8 + 2
= -6
The Correct Answer Is 90
the answer is -70. i took the test
i need help